FINANCIAL MANAGEMENT BASED ON PESANTREN; CENTRALIZED VS DECENTRALIZED SUPPLY PROCESS - Mundiri, Akmal; Sanafiri , Ahmad Nadif (Managere: Indonesian Journal of Educational Management, 2022)
This study aims to determine the financial governance of Islamic boarding schools where centralization and decentralization policies are the focus of this research. The research method uses qualitative research that is descriptive of a phenomenon that occurs at the research location. Data collection techniques used documentation, interviews, and observations with three steps, namely: data reduction (Data Condensation), data presentation (Data Display), and data verification (Data Verification). There is a problem where the change in decentralization policy to centralization in financial governance has an impact on the sustainability of pesantren education. From the results of the data analysis it can be concluded that in the financial management of Pondok Pesantren Nurul Jadid, financial governance is carried out through the process of financial planning, implementation, reporting, evaluation, and financial supervision. In this case, Islamic boarding schools need to issue a more decentralized financial policy direction in which regions and educational institutions can optimize their resources and be creative in managing their resources.